Bacterial cellulose/collagen hydrogel for wound healing - De Sousa Moraes, Paula Rodrigues Fontes; Saska, Sybele [UNESP]; Barud, Hernane [UNESP]; De Lima, Lais Roncalho; Da Conceicao Amaro Martins, Virginia; De Guzzi Plepis, Ana Maria; Ribeiro, Sidney Jose Lima [UNESP]; Gaspar, Ana Maria Minarelli [UNESP] (FapUNIFESP (SciELO), 2016)
This study compares a wound dressing based on bacterial cellulose/collagen (BC/COL) hydrogel in rat dorsum with commercial collagenase ointment and untreated wound. The hydrogel was characterized by Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Fourier transformed-Infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). According to the In vivo test and macroscopic evaluation, BC/COL hydrogel showed a better repair of wounds and promoted statistically significant differences of tissue repair between treatments on the 7th day after surgery. Better quality, quantity and orientation evaluation of collagen fibers (p=0.0001) were observed in the BC/COL hydrogel and collagenase ointment groups in relation to the control group. The BC/COL hydrogel promoted better wound healing than collagenase and the control group, therefore, it can be considered a potential wound dressing for skin regeneration.
Keywords: Bacterial cellulose; Collagen; Hydrogel; Tissue repair; Wound dressing